State minimum wage laws and newly diagnosed cases of HIV among heterosexual black residents of US metropolitan areas. (April 2019) - Cloud, David H.; Beane, Stephanie; Adimora, Adaora; Friedman, Samuel R.; Jefferson, Kevin; Hall, H. Irene; Hatzenbuehler, Mark; Johnson, Anna Satcher; Stall, Ron; Tempalski, Barbara; Wingood, Gina M.; Wise, Akilah; et al.
Abstract: This ecologic cohort study explores the relationship between state minimum wage laws and rates of HIV diagnoses among heterosexual black residents of U.S metropolitan areas over an 8-year span. Specifically, we applied hierarchical linear modeling to investigate whether state-level variations in minimum wage laws, adjusted for cost-of-living and inflation, were associated with rates of new HIV diagnoses among heterosexual black residents of metropolitan statistical areas (MSAs; n=73), between 2008 and 2015. Findings suggest that an inverse relationship exists between baseline state minimum wages and initial rates of newly diagnosed HIV cases among heterosexual black individuals, after adjusting for potential confounders. MSAs with a minimum wage that was $1 higher at baseline had a 27.12% lower rate of newly diagnosed HIV cases. Exploratory analyses suggest that income inequality may mediate this relationship. If subsequent research establishes a causal relationship between minimum wage and this outcome, efforts to increase minimum wages should be incorporated into HIV prevention strategies for this vulnerable population. Highlights: Results from a study using hierarchical linear modeling found a significant, inverse relationship between state minimum wage, and rates of newly diagnosed HIV cases among black heterosexuals, after adjusting for cost-of-living and controlling for confounders. Findings suggest that an inverse relationship exists between baseline state minimum wages and initial rates of newly diagnosed HIV cases among heterosexual black individuals, after adjusting for potential confounders. MSAs with a minimum wage that was $1 higher at baseline had a 27.12% lower rate of newly diagnosed HIV cases. Exploratory analyses suggest that income inequality may mediate this relationship.